The Role of the Informal Sector in Solid Waste Management in the GAMA, Ghana: Challenges and Opportunities - Oteng-Ababio, M. (Blackwell Publishing Ltd, 2012)
Solid waste is one of the most discussed environmental issues, especially in urban centres where both public and private sectors are active participants in its management. This increased attention has been due to the continuous insanitary and health threatening conditions, in spite of governments’ huge budgetary interventions. Meanwhile, for most urban poor, waste collection and recycling is a common means for eking out a living, yet this potential for improving solid waste management appears untapped by the authorities. Using mainly qualitative research techniques, this study examines the role of the informal sector and promotes dialogue on the potential of this sector in solid waste management. The findings show that the practice has become a survival strategy for thousands among the urban poor and that, the proper integration of the sector into the existing solid waste management policies can lead to sustainable management practices and possibly help alleviate poverty
Keywords: Private waste picker; environmental sanitation; sustainable development; GAMA; Ghana